Unity Artificial Intelligence Programming : Add Powerful, Believable, and Fun AI Entities in Your Game with the Power of Unity 2018!, 4th Edition. - Aversa, Davide (Packt Publishing Ltd, 2018)
Unity 2018 provides game and app developers with a variety of tools to implement Artificial Intelligence(AI). Leveraging these tools via Unity's API allows limitless possibilities for creating your game's worlds and characters. This edition will break down AI into simple concepts to give you a fundamental understanding of the topic to build upon.